A large-scale survey of inpatient suicides: comparison between medical and psychiatric settings. (April 2017) - Inoue, Keisuke; Kawanishi, Chiaki; Otsuka, Kotaro; Cho, Yoshinori; Shiraishi, Masaki; Ishii, Takao; Onishi, Hideki; Hirayasu, Yoshio
Abstract: Suicide is one of the common severe accidents occurring in hospitals. This study aimed to investigate inpatient suicides simultaneously in medical and psychiatric settings in a large number of hospitals and to examine the prevalence of common suicide risk factors, related symptoms in inpatients who had died by suicide and the differences in inpatient suicides between both settings. We conducted a survey of hospitals in Japan that belonged to the nationwide standard-setting and accrediting body. The questionnaire covered the: 1) presence or absence of inpatient suicides in each hospital from 2012 to 2015; 2) number of inpatient suicides; 3) method, location, and timing of inpatient suicides; and 4) characteristics of inpatients who died by suicide. In total, 529 hospitals reported 262 inpatient suicides during the 3-year period: 131 were in medical settings and 131 were in psychiatric settings. The prevalence of common suicide risk factors was frequent in inpatient suicides. Inpatients had characteristics and suicide risk factors specific to those settings such as worsening of physical health in medical settings. Therefore, recognizing common suicide risk factors and understanding differences in inpatient suicides between both settings are important to prevent inpatient suicides. Highlights: Inpatient suicide and its characteristics were investigated in 1376 hospitals. In medical settings, 20% of the hospitals investigated reported inpatient suicides. In psychiatric settings, 62% of the hospitals reported inpatient suicides. Worsening of physical health was considered a risk in patients in medical settings. Worsening of mental status was considered a risk in patients in psychiatric settings.